FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI GALANGAN KAPAL KAYU DI BAGAN SIAPI API KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Hardiansyah Hardiansyah; Harahap Azwar; Mardiana Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of raw materials, labor and capital on the wooden shipyard industrial production in Bagan Siapi Api, Bangko District, Rokan Hilir Regency. This study aims to determine the effect of raw materials, labor and capital on the wooden shipyard industrial production in Bagan Siapi Api, Bangko District, Rokan Hilir Regency. The population of the study was all 28 timber shipbuilding industry production business actors. The sampling technique in this study was a census in which the entire population was sampled, this is because the population was less than 100. Measurements carried out in this study were to use a questionnaire while the analysis technique was multiple linear regression analysis with the SPSS program. Based on the research results, it is found that labor has a significant effect on the production of the wooden shipyard industry in Bagan Siapi Api, Bangko District, Rokan Hilir Regency. Furthermore, capital has a significant effect on the production of the wooden shipyard industry in Bagan Siapi Api, Bangko District, Rokan Hilir Regency. Raw materials have a significant effect on the production of the wooden shipyard industry in Bagan Siapi Api, Bangko District, Rokan Hilir Regency. However, raw materials have the most dominant influence on the production of the wooden shipyard industry in Bagan Siapi Api, it can be seen from the Standardized Coefficient Beta test that the raw material variable has a large value.Keywords: Raw Materials, Labor, Capital, Production